The effects of integrated traditional Chinese and western medicine rehabilitation programs on post-acute ankle sprain: A randomized controlled trial study protocol - Hang Gao; Xiao Chen; Jiayi Ren; Xinglai Zhang; Yuqian Hu; Zhao Ma; Yuanjia Gu; Jiming Tao; Weian Yuan (PLoS ONE, 2025)
Background Ankle sprain is a common clinical disease, which has the highest incidence rate among joint and ligament injuries. And acute ankle sprains can easily develop into chronic ankle instability, thereby increasing the difficulty of treatment. The current clinical guidelines for post-acute ankle sprains are still controversial. Pain and functional impairment are the most significant symptoms after ankle sprain. The main purpose of this study is to explore the safety and effectiveness of the intervention of integrated traditional Chinese and Western medicine rehabilitation programs on post-acute ankle sprains. Methods This study is a single center, prospective, intervention randomized controlled trial with a control group. 174 patients of 18–35 years old with post-acute ankle sprain will be included. A randomized controlled study is conducted and divided into a control group and an experimental group. The control group receive routine treatment, while the experimental group receive integrated traditional Chinese and western medicine rehabilitation programs. The intervention lasted for a total of 2 weeks. The main outcome measures are Visual Analog Scale and Short Form McGill Pain Questionnaire; the secondary outcome measures are the Foot Ankle Ability Assessment Scale, AOFAS Ankle Posterior Foot Scale, torque and gait. This study protocol aims to evaluate the safety and effectiveness of integrated traditional Chinese and western medicine rehabilitation programs by comparing the results of two groups before and after treatment. This protocol will follow the SPIRIT guidance. Discussion At present, there is a lack of rehabilitation management for post-acute ankle sprains. Therefore, this study has the potential to improve the healthcare for post-acute ankle sprains patients and might be used for future standardized evidence-based rehabilitation concepts. Trial registration The trial was registered at Chinese Clinical Trial Registry https://www.chictr.org.cn/showproj.html?proj=234465 (Registration No.: ChiCTR2400087456). Date: 2024-07-29.